Soluble fms‐like tyrosine kinase‐1 to placental growth factor ratio: ruling out pre‐eclampsia for up to 4 weeks and value of retesting - Zeisler, H.; Llurba, E.; Chantraine, F. J.; Vatish, M.; Staff, A. C.; Sennström, M.; Olovsson, M.; Brennecke, S. P.; Stepan, H.; Allegranza, D.; Schoedl, M.; Grill, S.; et al. (Ultrasound in obstetrics & gynecology, 2019)
ABSTRACT Objectives The soluble fms‐like tyrosine kinase‐1 (sFlt‐1) to placental growth factor (PlGF) ratio is generally elevated some time before and at the clinical onset of pre‐eclampsia. The PROGNOSIS study validated a sFlt‐1/PlGF ratio cut‐off of ≤ 38 to rule out the onset of pre‐eclampsia within 1 week of testing in women with suspected disease. The aim of this study was to assess the predictive value of the sFlt‐1/PlGF ratio to rule out the onset of pre‐eclampsia for up to 4 weeks, and to assess the value of repeat measurements. Methods This was an exploratory post‐hoc analysis of data from the PROGNOSIS study performed in pregnant women aged ≥ 18 years with suspected pre‐eclampsia, who were at 24 + 0 to 36 + 6 weeks' gestation at their first clinic visit. Serum samples were collected at the first visit and weekly thereafter. sFlt‐1 and PlGF levels were measured using Elecsys® sFlt‐1 and PlGF immunoassays. Whether the sFlt‐1/PlGF ratio cut‐off of ≤ 38 used to rule out the onset of pre‐eclampsia within 1 week could predict the absence of pre‐eclampsia 2, 3, and 4 weeks post‐baseline was assessed. The value of repeat sFlt‐1/PlGF testing was assessed by examining the difference in sFlt‐1/PlGF ratio 2 and 3 weeks after the first measurement in women with, and those without, pre‐eclampsia or adverse fetal outcome. Results On analysis of 550 women, sFlt‐1/PlGF ratio ≤ 38 ruled out the onset of pre‐eclampsia 2 and 3 weeks post‐baseline with high negative predictive values (NPV) of 97.9% and 95.7%, respectively. The onset of pre‐eclampsia within 4 weeks was ruled out with a high NPV (94.3%) and high sensitivity and specificity (66.2% and 83.1%, respectively). Compared with women who did not develop pre‐eclampsia, those who developed pre‐eclampsia had significantly larger median increases in sFlt‐1/PlGF ratio at 2 weeks (∆, 31.22 vs 1.45; P < 0.001) and at 3 weeks (∆, 48.97 vs 2.39; P < 0.001) after their initial visit. Women who developed pre‐eclampsia and/or adverse fetal outcome compared with those who did not had a significantly greater median increase in sFlt‐1/PlGF ratio over the same period (∆, 21.22 vs 1.40; P < 0.001 at 2 weeks; ∆, 34.95 vs 2.30; P < 0.001 at 3 weeks). Conclusion The Elecsys® immunoassay sFlt‐1/PlGF ratio can help to rule out the onset of pre‐eclampsia for 4 weeks in women with suspected pre‐eclampsia. © 2018 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.